A CRITICAL ANALYSIS OF LANGUAGE USE AND LANGUAGE ACQUISITION - Alikberova, Kamila (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
This article provides a critical analysis of language use and language acquisition, exploring their intricate relationship and shedding light on key theoretical and empirical debates in the field. Drawing upon research from various disciplines, including linguistics, psychology, and sociology, the article examines the social, cognitive, and cultural aspects of language use and acquisition. It delves into the complexities of language as a multifaceted phenomenon that both shapes and is shaped by individual and social factors. The critical analysis encompasses topics such as pragmatics, discourse analysis, language and thought, and intercultural communication, among others. By critically examining these areas, the article aims to deepen our understanding of how language is used, acquired, and experienced, and to foster insights into language-related issues in diverse contexts.